PROSES SCAFFOLDING PADA ZONE OF PROXIMAL DEVELOPMENT (ZPD) DALAM PEMBELAJARAN - I Putu Suardipa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Vygotsky learning theory is a view that can accommodate sociocultural-revolution in the theory of learning. Vygotsky theory learning is one of the social learning theories so that it is very suitable for cooperative learning model because in cooperative learning model occurs social interactive, namely interaction between students and students and between students With the teacher, in an effort to discover concepts and problem solving. During this interaction process there is cognitive apprenticeship, which is the process by which one who is learning step by step gaining expertise through interactions with experts. Vygotsky's theory assumes that learning occurs when children work or learn to handle unlearned tasks but those tasks are still within reach of their abilities, or those tasks are in the zone of proximal Development. Zone of proximal development is a slight development of students ' capabilities over their own capabilities. Vygotsky emphasizes scaffolding, which is to provide full assistance to the child in the early stages of learning which is then gradually reduced and gives the child the opportunity to take over the greater responsibility immediately After he can do it.Keywords: Scaffolding Process, Zone of Proximal Development, Vygotsky learning theory